Accountability through integrated reporting: the awareness and challenges in Malaysia / Nor Farizal Mohammed … [et al.] - Mohammed, Nor Farizal; Che Kassim, Che Fatimah; Sutainim, Nor Aqilah; Amirrudin, Mira Susanti (Faculty of Accountancy, 2019)
Integrated reporting is a form of innovative reporting that has marked another milestone in the financial reporting environment. The aim of integrated reporting is to enhance accountability and stewardship to the stakeholders by emphasizing on the six capitals, namely financial, manufacturing, intellectual, natural, human and social and explaining their interdependencies in creating values for the business over time. Integrated reporting promotes integrated thinking and decision making by focusing on the true value drivers of business. As Malaysia is striving to be a global capital market, it is vital for the country to keep in pace with the international development in enhancing transparency and accountability, by moving towards integrated reporting. While the status of integrated reporting is voluntary, integrated reporting in Malaysia is fairly new. Therefore, there is a need to raise the awareness on integrated reporting in the country. The objectives of this paper are twofold: the first objective is to critically analyze the literature of integrated reporting in clarifying the role and form of integrated reporting; and the second objective is to survey on the awareness of Malaysian accountants about integrated reporting. The general understanding of integrated reporting is a combination of financial reporting and sustainability reporting. The review of literature clarifies and provides a better platform to understand the concept of integrated reporting. The results of the survey revealed that generally, Malaysian accountants are not clear about the concept of integrated reporting. This study contributes by giving insights to the regulators on the state of readiness and awareness of Malaysian accountants regarding the implementation of integrated reporting.